Hubungan Tingkat Pengetahuan Dan Motivasi Dengan Kepatuhan Minum Obat Anti Tuberkulosis Pada Penderita TB Paru Di Rumah Sakit An-Nisa Tangerang - Clara Aulia Rachmah; Adi Dwi Susanto; Imas Sartika (PT. Padang Tekno Corp, 2023)
Background: Pulmonary tuberculosis (pulmonary TB) is a chronic infectious disease caused by the bacterium Mycobacterium tuberculosis. Mycobacterium tuberculosis is a bacterium that causes tuberculosis infection which is transmitted by droplet splashes and becomes a vector of transmission when a person interacts physically. Objective: This study aims to determine the relationship between the level of knowledge and motivation with adherence to taking anti-tuberculosis medication at An-Nisa Hospital Tangerang. Methods: This study used descriptive analytic quantitative research with a cross sectional approach. The sampling technique used was purposive sampling method, where this technique selected subjects in a population that matched the criteria as a sample, namely pulmonary TB patients who were undergoing initial and advanced treatment at An-Nisa Hospital, Tangerang, totaling 102 respondents. Data analysis was performed using the chi-square test. Results: The results of the respondent's data processing showed that the level of knowledge with adherence to taking anti-tuberculosis medication showed a significant relationship with value (p-value 0.021), and motivation with adherence to taking anti-tuberculosis medication showed a significant relationship with value (p-value 0.027 ). Conclusion: It can be concluded that there is a relationship between the level of knowledge and motivation with adherence to taking anti-tuberculosis medication in patients with pulmonary TB. Therefore, to reduce the occurrence of drug-resistant TB, efforts should be made to increase adherence to treatment in TB patients, either through the method of providing direct motivation or through counseling about pulmonary TB disease.